Increasing the Possibilities of TEMPO‐Mediated Oxidation in the Production of Cellulose Nanofibers by Reducing the Reaction Time and Reusing the Reaction Medium. (29th January 2021) - Sanchez‐Salvador, Jose Luis; Campano, Cristina; Negro, Carlos; Monte, M. Concepcion; Blanco, Angeles
Abstract: 2, 2, 6, 6‐Tetramethylpiperidine‐1‐oxyl (TEMPO)‐mediated oxidation of cellulose is the most effective pretreatment to obtain highly fibrillated cellulose nanofibers (CNFs). However, the associated environmental impact and the high operational costs have limited its implementation at large scale. This study aims to improve the effectiveness of this pretreatment by reducing the oxidation time and reusing the reaction medium, with the ultimate objective of upscaling a more viable sustainable process. The results show the possibility of reducing the reaction time by 85% and 60% in the case of cotton and eucalyptus pulps, respectively, without altering the properties of the obtained CNFs (carboxyl groups, nanofibrillation yield, cationic demand, and morphology). The reuse of 75% of the reaction medium for ten cycles, do not alter the properties of the CNFs either. With this approach, the consumption of TEMPO and NaBr is reduced by 67%, while that of NaClO is decreased by 42% and 22% in the oxidation of cotton and eucalyptus cellulose, respectively. At the same time, the environmental concerns derived from the disposal of the catalysts are considerably reduced. Abstract : This study improves the efficiency and sustainability of the TEMPO mediated oxidation process to produce cellulose nanofibers (CNFs). The reaction medium is reused ten times, observing no variation in the CNF properties. The catalyst load and reaction time are reduced by 67.5% and 60–85%, respectively. With this approach, the environmental impact and the operational costs are reduced.